Analisis Komparatif Sosiodemografi Terhadap Kepatuhan Penggunaan Antihipertensi Pada Pasien Hipertensi RSUD Puri Husada Tembilahan - Husnawati Husnawati; Erniza Pratiwi; Yellia Syafitri; Cindy Oktaviana Laia; Reni Zulfitri (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Hypertension is a condition where systolic blood pressure increases to more than 140 mmHg and diastolic blood pressure to more than 90 mmHg. Compliance with antihypertensive medication is crucial. Hypertension cannot be cured and must be consistently monitored to prevent complications that can lead to death. One of the factors that can affect the level of medication adherence in patients is the patient's sociodemographics including age, gender, educational level and employment status. The purpose of this study was to analyze the effect of sociodemography on compliance with antihypertensive use in hypertensive patients at Puri Husada Tembilahan Hospital. This research is an observational study with a cross-sectional research design with analytic descriptive method. The sample in this study were patients with a primary diagnosis of hypertension with or without comorbidities who went to the Puri Husada Tembilahan Hospital at the time of the study and met the inclusion criteria. Based on the results of the study it was found that of the 4 sociodemographic aspects studied, namely age, gender, education level and employment status, only education level affected the level of adherence to taking medication in hypertensive patients (P value = 0.000), where respondents with higher education levels had higher levels of higher adherence than respondents with low levels of education.